ANALISIS FAKTOR YANG DIPERTIMBANGKAN KONSUMEN DALAM KEPUTUSAN MEMILIH JASA PENDIDIKAN SEKOLAH MENENGAH ATAS (SMA) - Sona, Batara Ari (Manajemen Bisnis, 2018)
The purpose of this study was (1) to examine the factors that considered by consumers in deciding secondary education level in SMAN 3 Malang and (2) to examine the dominant factor that considered by consumers in deciding secondary education level in SMAN 3 Malang. This study applied quantitative with descriptive design. The population of the study was tenth class of SMAN 3 Malang. The data were analyzed by using factor analysis. The results of the study showed that (1) there were 4 factors that considered by consumers to decide secondary education level in SMAN 3, namely product, process, physical evidence, and personality and (2) the most dominant factor that considered by consumers to decide secondary education level in SMAN 3 was product quality.